Attention training technique delivered in groups as treatment for anxiety and depression in patients with coronary heart disease: study protocol for a waiting-list randomized controlled trial - Dammen, Toril; Tunheim, Kristoffer; Munkhaugen, John; Klungsøyr, Ole; Papageorgiou, Costas (Frontiers in Psychology, 2023)
Clinically sSignificant symptoms of depression and anxiety in coronary heart disease (CHD) patients are common and associated with adverse outcomes. Psychological treatments have shown limited effectiveness and more effective treatments have been requested. Attention training technique (ATT), a component of metacognitive therapy, can potentially be as effective as a stand-alone treatment compared to the full metacognitive therapy in the treatment forof anxiety and depression. In an open study, ATT delivered face-to-face in a group format was feasible and potentially effective for improving depression and anxiety symptoms in CHD patients. The next progressive step is to test the effectiveness of ATT in a randomized controlled trial. This paper describes the methodology of this trial.ATT-CHD is a randomised wait-list (WL) controlled study. Eligible CHD patients from two hospitals with Hospital Anxiety and Depression Scale (HADS)-Anxiety and/or HADS-Depression subscales scores >8 will be randomised into ATT (n=32) or WL control (n=32).After 6-8 weeks, WL patients will be allocated to ATT. Participants will be evaluated pre-, mid-and post-treatment, and at 6-months follow-up using changes in HADS as primary outcome. Secondary outcomes will be changes in psychiatric disorders, rumination, worry, type D-personality, metacognitions, insomnia, quality of life, and C-Reactive protein (CRP).To our knowledge, this will be the first WL-controlled randomized study testing the effectiveness of group-based ATT as treatment of symptoms of anxiety and depression in CHD patients. It will also explore correlations between changes in psychological distress and CRP. A qualitative analysis will reveal patients' experience with ATT including processes that may facilitate or serve as barriers to effectiveness. RecruitmentInclusion into the study commenced in December 2022.The Regional Committees for Medical and Health Research Ethics (REK), Norway has granted approval for the study (ID 52002). The trial results will be published in peer-reviewed journals. According to Norwegian legislation, the Norwegian Data Protection Authority, and the Committee of Ethics, we are not allowed to share original study data publicly.Clinical Trial Registration: Clinicaltrials.gov, identifier NCT05621408 pre-inclusion. There were no significant changes of methods or outcomes after study start.